Towards effective universality of fundamental rights by rethinking subsidiarity and mutual trust in the EU - Pretelli, Ilaria (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
This paper establishes a connection between the growing influence of supranational bodies on domestic law and the substantial and institutional crisis of international law. A series of emblematic cases demonstrates that it is increasingly unrealistic to limit multinationals to compliance with private law, particularly in the European Union, where unified private international law and the principle of mutual trust risk being used strategically under the pretext of technical neutrality to depoliticise solutions that favour private economic interests. To resolve the tension between supranational legal integration and local social interests, it is proposed to re-establish the principle of subsidiarity in its original sense as a tool to balance supranational cohesion with the capacity of national communities to contribute in diverse ways to the creation of a truly universal corpus of fundamental rights and world peace. The article concludes by proposing a diachronic interpretation of fundamental rights which, while respecting cultural diversity, guides the development of transnational law towards social justice and world peace rather than facilitating the expansion of global markets